Genetic diversity in the Andes: variation within and between the South American species of Oreobolus R. Br. (Cyperaceae) (2017)
This study examines genetic relationships among and within the South American species of Oreobolus that span the temperate and tropical Andes hotspots and represent a good case study to investigate diversification in the Páramo. A total of 197 individuals covering the distributional range of most of these species were sequenced for the nuclear ribosomal internal transcribed spacer (ITS) and 118 individuals for three chloroplast DNA regions (trnL-F, trnH-psbA and rpl32-trnL). Haplotype networks and measures of genetic diversity were calculated at different taxonomic and geographic levels. To test for possible geographic structure, a spatial analysis of molecular variance (SAMOVA) was undertaken and species relationships were recovered using a coalescent-based approach. Results indicate complex relationships among the five South American species of Oreobolus, which are likely to have been confounded by incomplete lineage sorting, though hybridization cannot be completely discarded as an influence on genetic patterns, particularly among the northern populations of O. obtusangulus and O. cleefii. We report a case of cryptic speciation in O. obtusangulus where northern and southern populations of morphologically similar individuals are genetically distinct in all analyses. At the population level, the genetic evidence is consistent with contraction and expansion of islands of Páramo vegetation during the climatic fluctuations of the Quaternary, highlighting the role of these processes in shaping modern diversity in that ecosystem. © 2017, Swiss Botanical Society.